Bergson o aspektach poznawczych zagadnienia porządku, nieporządku, niebytu, nicości, niczego w systemowym ujęciu rzeczywistości - Pezdek, Krzysztof (Er(r)go. Teoria - Literatura - Kultura, 2007)
The article explores Henri Bergson’s philosophical works from the perspective of the significance of cognitive aspects of the issues of order and disorder.